Transcatheter aortic valve‐in‐valve implantation for failed surgical bioprosthetic valves. A minimalist approach without contrast aortography or echocardiographic guidance. Issue 1 (30th April 2019) - Attinger‐Toller, Adrian; Htun, Nay M.; Murdoch, Dale; Perlman, Gidon Y.; Alenezi, Abdullah; Sathananthan, Janarthanan; Blanke, Philipp; Leipsic, Jonathon; Thompson, Christopher; Ye, Jian; Cheung, Anson; Wood, David; et al.
Abstract: Objectives: To demonstrate safety, feasibility and short‐term clinical outcomes after transcatheter aortic valve‐in‐valve (ViV) implantation under local anesthesia without contrast aortography or echocardiographic guidance. Background: Transcatheter ViV implantation is an emerging treatment modality for patients with degenerative surgical bioprostheses. Given the radiopaque properties of the surgical aortic valve (SAV) frame, ViV procedures can often be performed with fluoroscopic guidance alone. Methods: ViV implantation was performed in 37 patients with SAV failure under local anesthesia without contrast aortography. Clinical and echocardiographic data were obtained at baseline, discharge, and 30 days. Results: Mean age was 74 ± 10 years and STS predicted risk of mortality was 5.6 ± 2.4%. Mean transaortic gradient decreased from 39.4 ± 15.5 mmHg to 13 ± 6.3 mmHg at discharge ( p < .001), and 20 ± 7.5 mmHg at 30 days ( p < .001 compared to baseline), aortic valve area increased from 0.9 ± 0.3 cm 2 to 1.2 ± 0.4 cm 2 at 30 days ( p = .007). No patient had more than mild aortic regurgitation. Hospital discharge occurred at a median of 2.6 ± 4.4 days. At 30‐day follow‐up there were no deaths, myocardial infarctions, strokes, repeat hospital admissions for heart failure, or renal failure. One patient (2.7%) required a new pacemaker. 93% of the patients were in New York Heart Association functional class I or II. Conclusions: Transcatheter aortic ViV implantation for selected patients with degenerative surgical bioprostheses under local anesthesia without aortography or echocardiographic guidance is feasible and safe.